Meditation as a Potential Spiritual Tourism in Bali - Bagus Nyoman Mantra, Ida; Adi Susrawan, I Nyoman; Dwi Handayani, Nengah (Journal of Indonesian Tourism and Development Studies, 2024)
Spiritual tourism is one of the tourism assets that can be developed to support sustainable tourism in Bali. Spiritual tourism is a type of tourism that is undertaken by individuals to seek peace, tranquility, and harmony with body, mind, and soul. Meditation activities can be utilized to promote spiritual tourism and attract both domestic and international tourists. This study explores the potential of meditation as a spiritual tourism attraction in Bali. This study used a qualitative research method with descriptive analysis to reveal meditation activities and their potential for spiritual tourism in Bali. The data were collected through interviews with tourism stakeholders, meditation practitioners, and visitors to Bali. The study found that meditation attracts many visitors to deepen their spiritual knowledge and gain calmness, happiness, and harmonious feelings. Moreover, meditation can be an alternative tourism activity that attracts visitors to Bali and encourages them to stay longer. The study's findings provide a significant contribution to the tourism industry in developing sustainable tourism in Bali. Therefore, the study implies that meditation can be utilized to promote the tourism development program in Bali